2014
DOI: 10.1007/s00380-014-0537-0
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac blood supply–workload balance in children

Abstract: It is well known that the reflected pressure wave in small children returns earlier than that in adolescent. The reason of early return of the reflected pressure wave in infancy is their height.The short distance between heart and reflection point makes the reflected pressure wave returning to the heart earlier. In adult, the early return (during systole) of the reflected pressure wave means disadvantage to cardiac blood supply-workload balance. The purpose of this study is to clarify whether the early return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Moreover, it has been previously reported that lowest SEVR in children was associated with early return of reflected pressure waves. 17 In the present study, cAP was not different between groups and, hence, there is no evidence of shorter wave reflection time among overweight/ obese to explain the differences found. On the other hand, heart rate derived from the pulse wave recording was higher among overweight/obese girls, which caused the time spent with diastole be shorter in this group.…”
Section: Funding Informationcontrasting
confidence: 67%
“…Moreover, it has been previously reported that lowest SEVR in children was associated with early return of reflected pressure waves. 17 In the present study, cAP was not different between groups and, hence, there is no evidence of shorter wave reflection time among overweight/ obese to explain the differences found. On the other hand, heart rate derived from the pulse wave recording was higher among overweight/obese girls, which caused the time spent with diastole be shorter in this group.…”
Section: Funding Informationcontrasting
confidence: 67%
“…Figs 3 and 4 show the agreement between the computed pressure and flow rate and those given in literature for both the systemic and pulmonary circulation. In particular, Fig 3 shows the physiological aortic pressure and flow rate calculated by the 0D model together with published in vivo measurements obtained in paediatric subjects [19,20]. There is a good PLOS ONE [22,23].…”
Section: Resultsmentioning
confidence: 94%
“…Panel (a): 0D model results for the physiologic case (aortic pressure, red curve; aortic flow rate, blue curve). Panels (b) and (c): published in-vivo data (aortic Doppler velocity waveform[19] and aortic pressure[20]). Note that, by assuming a constant valve area, the velocity waveform resembles the flow one except for the absolute values and the scale.https://doi.org/10.1371/journal.pone.0258225.g003…”
mentioning
confidence: 99%
“…Other correlating central haemodynamic parameters are partly dependent on the HR, so we are of opinion that their correlation is also a consequence of the physiological state. Murakami et al [19] also showed a positive relationship between SEVR and age in children. Our prediction is supported by the fact that the results of other kidney function markers do not show an association with central haemodynamic parameters.…”
Section: Discussionmentioning
confidence: 95%
“…Alx is, like PWV, a measure of systemic arterial stiffness derived from the ascending aortic pressure waveform. It is calculated from pulse wave reflection pressures as the augmentation pressure divided by the pulse pressure [18, 19].…”
Section: Methodsmentioning
confidence: 99%